Full responsibility on pragmatic, political, and other modes of sharing action - Smith, Steven G. 1953- (Suny series in American philosophy and cultural thought, 2022)
"Explores the basic forms of responsibility that we willingly assume and the collaborative fulfillment that we find in each"--